PENDEKATAN PLACEMAKING DALAM PERANCANGAN RUANG PUBLIK YANG LAYAK HUNI DI KELURAHAN KALIANYAR, JAKARTA - Prabowo, A Hadi; Gandarum , M. Dedes Nur; Hartanti, Nurhikmah Budi; Murwonugroho, Wegig; Moertiningsih, Sarwosri; Milvan, Tania Ansarah Davina (Jurnal AKAL: Abdimas dan Kearifan Lokal, 2025)
The arrangement of dense residential areas is a National Housing and Settlement issue as stated in the 2020-2024 National Medium-Term Development Plan (RPJMN) and part of the global agenda that has been formulated by UN Habitat. Public space in densely populated areas is one of the programs to improve the quality of the residential environment, which plays a role in encouraging social interaction of citizens in order to create a sense of togetherness, solidarity and social cohesion. RW 07 Kalianyar Village, Tambora District, DKI Jakarta is a dense area that requires the provision of public space as an effort to improve the quality of the physical environment. The community service (PKM) program of 2021-2022 departs from an evaluation of the results of the previous PKM program. The structuring approach used is placemaking, namely the arrangement of public space by considering the needs of social interaction, activities, comfort, image, accessibility, as well as creating a sense of comfort, security against crime and health. Arrangement planning is carried out using a participatory planning approach through community consultations or Focus Group Disscussion (FGD), and identification of needs through field observations involving the community or the Village Own Survey. In the previous PKM, a public space has been created that utilizes the space above the channel, by following the health protocol to anticipate the Covid 19 pandemic condition. Based on the evaluation, the community is very enthusiastic about the existence of this public space and uses it for various activities involving various age groups. This shows that the existing public space has succeeded in encouraging social interaction. However, residents still need public spaces that are safer and have educational benefits. Therefore, the solution proposed in this PKM is to plan a reading room, with the addition of a gate at the end of the alley leading to the public space and the addition of a roof using lightweight materials. In addition, it is also planned to make interesting and educative wall murals to encourage the creativity of local children and youth.)